Psychiatric morbidity in absentees in industry - Indla Ramasubba Reddy (Wolters Kluwer Medknow Publications, 2021)
Background: Absenteeism refers to a worker's unscheduled absence from the workplace. Around the world, a large share of mental disorders can be attributed to work productivity losses. Despite industries working on improvement in employees' wages, better work environment and improved health care to improve their mental health. Absenteeism continues to be a global burden. Aim: The aim of the study was to explore the factors influencing absenteeism. Materials and Methods: A sample size of 100 workers was selected and standardized, and reliable research tools were employed. Factors influencing absenteeism such as the sociodemographic factors, personality traits, psychiatric morbidity, family typology, and interactions were studied using relevant scales, i.e., Eysenck's Personality Inventory and Family Typology by Batti and Channabasavanna. Results: Study found that absentees were more emotionally stable, whereas regulars were found to be emotionally unstable. Factors were found to be associated with absenteeism such as low income, 11–20 years of service, low mean neuroticism score, chronic physical disease, high psychiatric morbidity among the workers, egoistic and anomic family typology. This study reveals that a significantly higher proportion of absentees had a low pay scale. Paradoxically, a high proportion of absenteeism had a longer duration service, indicating that the low pay scales could have resulted from disciplinary actions against absentees, like loss of increments, etc. Conclusion: Psychosis, alcoholism, and chronic physical illnesses are among the illnesses which contribute to absenteeism.